Use of Metalfom Wall to response Light Steel Frame (LSF) structures Risk - Hashem Shariatmadar (Iranian Society of Structrual Engineering (ISSE), 2018)
Light Steel Frame System that is briefly called LSF is a building system which is used for implying of short-rise and mid-rise buildings (up to five floors). This system gets significant benefits, although in our country it is not much used. So in this article, are tryed to study LSF structures from the design and implementation stage to the operation one and identify its risks exactly and evaluate them with combination technique which used failure modes and effects analysis technique‌ (FMEA) and fuzzy method.Then express new idea for implementation of LSF structures that optimizes time, cost and quality and can be respond of many Identified risks.This idea named Metalfom Walls that included in systems verificated BHRC. In this article are explained this system first, then combination of Metalfom and LSF system are discussioned. The result of this combonation in aspect of cost, time ,weight of structure and conditions of implementation are explained. Comparison of results in aspect of cost, time and weight of structure by Analytic hierarchy process technique (AHP) are evaluated. Results of this evaluation show that combination of Metalfom system and Light Steel Frame System (LSF) earns 54 score and LSF system that implementated in common way earns 46 score.